INSTITUTIONAL FACTORS FOR STAFF POTENTIAL’ FORMATION FOR THE COMPETITIVENESS DEVELOPMENT OF THE REGION - Kropelnytska , S.O.; Mayorova , T.V.; Kondur , O.S. (The actual problems of regional economy development, 2019)
The article explores the issues of the institutional component of the region's competitiveness in terms of the formation of personnel (human) potential for its development. The goal is to investigate the institutional factors of capacity building of personnel potential at the regional level and to suggest ways of its development on the basis of the project “Creating a Project and Educational Center for innovations and investments in the region” in order to increase the level of competitiveness and innovation of the development of the Carpathian region of Ukraine. To receive qualitative and quantitative results of the research, used in the article - methodology of the sociological survey, in particular when calculating the indicator scharacterizing the human resources of the Prykarpattya’ communities; methods of statistical information processing, logical and analytical have been applied – for outlining trends of formation, for definition and systematization of data on personnel potential, which is formed at the Vasyl Stefanyk Precarpathian National University (PNU), in the context of Amalgamated Territorial Communities (ATC) of the Ivano-Frankivsk region, in the context university institutes and faculties etc. The problem that is being investigated in the article, and which needs to be solution, conditioned of absence of balance between supply and demand for relevant staff, who prepared by higher education institutions (HEIs) for the communities of the region. The problem is solved by the creation of educational institutions in Higher Education Institutions. They will play the role of the administrative centers of interaction of Higher Education Institutions (HEI) – Amalgamated territorial community (ATC) for information gathering and decision-making on formation of personnel potential of development of competitiveness of region. The practical significance of this research is that it is carried out within the framework of an existing regional development project and based on the primary results of the activities of Project and Educational Center for the Development of Innovations and Investments in the Region – “Agents of Changes” PNU. The scientific novelty and value is the development of methodological approaches to creating and implementing a network model of interaction HEI-ATC to formulate the region's human resources required by the community, also recommendations for formalizing short- and medium-term forecasts for the region.